Proposal for a comprehensive environmental key performance index of the green supply chain - Rodríguez Aguilar, Román (My University, 2020)
The consideration of environmental objectives in the design of green supply chains creates the need to build a set of key performance indicators for monitoring and control. There is a set of generally accepted environmental indicators for monitoring environmental objectives in the supply chain. However, so far these indicators have been disconnected from the operational and economic indicators of the supply chain. It is important to consider these elements in the integral performance of a green supply chain. The present work is a proposal of a general index of environmental performance that includes operational, financial, and environmental aspects that allow monitoring the integral performance of the supply chain by applying Principal Component Analysis of mixed data. © 2020, Springer Science+Business Media, LLC, part of Springer Nature.
Keywords: Environmental key performance indicator; Green supply chain; Principal component analysis of mixed data; Singular value decomposition; Benchmarking; Environmental management; Principal component analysis; Economic indicators; Environmental aspects